Therapeutic circle of black womans: A proposal for clinical-ethical-political listening for peripheral black women - Carolina Barros Silva, Ana (Revista Desenvolvimento Social, 2021)
Since its foundation in 2016, the Therapeutic Circle of the Black Womans has carried in its existence and resistance a denunciation: the psychic illness of the black, poor and peripheral people is a political project. We chose to listen to, care for and welcome black women living in peripheral neighborhoods of the city of São Paulo as a clinical, ethical and political position. The same positioning also permeates the decisions about the composition of our clinical body: we are black psychologists involved in the antirracist struggle who understand affection, care, and attention to mental health as political issues, agendas of struggle and daily militancy, as well as tools to produce new possible horizons for our people. In this sense, the Therapeutic Circle of the Black Womans believes that to build other senses and logics of social dynamics, we need to be, at the same time, committed to the clinic, as well as to the political struggle for social transformation and radical equality.